Makna Klausa "Orang-orang yang telah lama ditentukan untuk dihukum" Menurut Yudas 1:4 - Teguh Purwanto, Ani; Lulu , Isac; Tempa, Gladys (JURNAL ILUMINASI, 2025)
The phrase "those who were long ago appointed to damnation" in Jude 1:4 is often used as the basis for the concept of double predestination in Calvinism. However, this interpretation has sparked controversy among theologians. Some understand the text as evidence of predestination, while others see it as a warning of the consequences of punishment for those who reject God and Jesus Christ and follow false teachings. This study focuses on this phrase through exegetical methods using various analytical approaches: contextual, grammatical, structural, historical, lexical, exegetical, and theological. The results show that Jude 1:4 does not speak of double predestination, but rather of the certainty of punishment for those who abuse God's grace. Thus, this text emphasizes God's justice and the reality of punishment for disobedience, rather than the dual determination of salvation and destruction. Therefore, Jude 1:4 cannot be used as a theological basis for the doctrine of double predestination; instead, it must be understood as a warning against false teachings and the misuse of grace in the lives of believers.